The Possibility to Use Medications Purchased at the Expense of a Patient in Intensive Care Units of Healthcare Institutions - O. Yu. Aleksandrova; A. A. Sokolov (Общая реаниматология, 2017)
The purpose of the study: to identify a legally justified possibility for a patient (patient's relatives) to purchase a drug product (DP), which has not been purchased by a healthcare institution but is recommended by the doctor in charge «by lifesaving indication» as the most effective one.Materials and methods. Federal Law N 323-FZ «On the Fundamentals of Health Protection in the Russian Federation» as of 11/21/2011 and a number of current normative legal acts (NLA) regulating medical activities were analyzed.Results. The analysis demonstrated the absence of a concept of «lifesaving indications» in the normative legal acts. It demonstrated that the patient's illness that may require the prescription of DP by the «lifesaving indications» should be diagnosed by medical consultants' board of the healthcare institution. It also prescribes DPs «for lifesaving indications» not included in the standard of care (SC) and in the List of Essential Medicines (LEM) and not payable «outpocket of» (personal) funds.Conclusion. The use of DPs «for lifesaving indications» in urgent and emergency medical care should not be arranged on a feepaying basis. If a patient (or patient's relatives) would demand compensation for material damage (cost of purchased drug) by applying to a Obligatory Medical Insurance Company or bringing the case before the court, this demand should be satisfied.